(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Experimental investigation were carried out on single cylinder four stroke direct injection diesel engine operated in duel fuel mode using rice bran methyl ester (ROME) AND coconut shell derived producer gas . Rome is used as a pilot injected fuel which ignites the producer gas and air mixture when subjected to higher compression ratio .in order to study the effect of nozzle geometry on the performance of duel fuel engine an effort has been made to enhance the performance of a duel fuel engine utillizing different nozzle orifice.